2014
DOI: 10.1111/ppe.12120
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Birth Certificate‐Derived Maternal Weight Data

Abstract: Background Studies using vital records-based maternal weight data have become more common, but the validity of these data is uncertain. Methods We evaluated the accuracy of prepregnancy body mass index (BMI) and gestational weight gain (GWG) reported on birth certificates using medical record data in 1204 births at a teaching hospital in Pennsylvania from 2003 to 2010. Deliveries at this hospital were representative of births statewide with respect to BMI, GWG, race/ethnicity, and preterm birth. Forty-eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(134 citation statements)
references
References 29 publications
5
129
0
Order By: Relevance
“…These factors could lead to important differences in the accuracy of maternal weight data on birth certificates. Nevertheless, our study suggests that the degree of error is similar to what we and others previously observed among singletons (Bodnar et al 2014) (Vinikoor et al 2010; Park et al 2011; Wright et al 2012). …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These factors could lead to important differences in the accuracy of maternal weight data on birth certificates. Nevertheless, our study suggests that the degree of error is similar to what we and others previously observed among singletons (Bodnar et al 2014) (Vinikoor et al 2010; Park et al 2011; Wright et al 2012). …”
Section: Discussionsupporting
confidence: 91%
“…This method is unlikely to lead to significant bias in our validation results because there is a strong correlation between measured prepregnancy weight and prepregnancy weight recalled at the first visit (Lederman & Paxton 1998; Phelan et al 2011; Mandujano et al 2012). Furthermore, we previously demonstrated in singletons that the agreement proportions for birth certificate-derived BMI and GWG categories with medical-record categories were similar when we used measured weight at ≤8 weeks or prepregnancy weight recalled at the first visit (Bodnar et al 2014). …”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations